1 gives us
y=0 or y=1
2 gives us the same.
Had 2 resulted in y=0 or y=2, would the answer have been C? cause y=0 is common in both statements ?
Please, DO NOT
post pictures of questions. Rule #6 here: rules-for-posting-please-read-this-before-posting-133935.htmlWhat is the value of \(y\)?
(1) \(y^3+2y=y+2y^2\). Rearrange and factor out \(y\) to get \(y(y^2-2y+1)=0\), which is the same as \(y(y-1)^2=0\), so \(y=0\) or \(y=1\). Not sufficient.
(2) \(y^2=y\). The same two solutions: \(y=0\) or \(y=1\). Not sufficient.
(1)+(2) Nothing new. Not sufficient.
As for your question: if from (2) we had that y=0 or y=2, then the answer would be C: y=0.
Sorry Sir, Will adhere to rule 6 going forward.
Thanks for the reply..